KETAHANAN SOSIAL NELAYAN: UPAYA MERUMUSKAN INDIKATOR KERENTANAN [VULNERABILITY] TERKAIT DENGAN BENCANA PERUBAHAN IKLIM - Wahyono, Ary (Masyarakat Indonesia, 2018)
Studies on the impact of climate change on the vulnerability of fishermen communities are still rare. The vulnerability studies highlight the physical dimensions whereas the social dimensions with climatic change are rarely performed. This paper attempts to obtain an understanding about the issue of the vulnerability of fishermen communities with climate change context. Vulnerability caused as a result of climate change is an important component of any effort to determine the magnitude of the threat posed by its natural phenomenon. Measuring the social vulnerability indicators starts from the understanding about social vulnerability refers to the exposure that is an exposure acceptance of a danger or stress conditions in groups or individual level. The level of social vulnerability is strongly influenced by access factor to natural resources and diversity of income sources. Vulnerability changes all the time, both in short or long term, depending on how much adaptation changes, as in the character threats, exposure to the threats, sensitivity, and capacity to response or recovery efforts that produce results quicker. Vulnerability analysis is useful for determining the effective instrument to propose the corrective actions with defensive strategies and facilitate the adaptation. One of the important things is vulnerability happens when the fishermen do not have the anticipation capacity to make any adjustments or efforts to overcome the impact of natural disasters due to weather anomalies or extreme weather. Reduced income plus the growing debt-ridden life sustaining household is vulnerability characteristic. Meanwhile, there is no mechanism solutions to overcome the marginalization of fishermen, there is no diversification of the fishing gear, and no other activities outside the fishery. The social relations pattern on a patron-client fishing community does not help fishermen (workers) from the slump caused by climate change. Collectivity do not provide an insurance for lower groups, while institutional foundations are underprivileged to provide social durability to fishermen communities as a whole.